A phase I, randomized, single-dose pharmacokinetic study comparing sb8 (bevacizumab biosimilar) with reference bevacizumab in healthy volunteers - Shin, Donghoon (Cancer Chemother Pharmacol, 2020)
PURPOSE: To compare pharmacokinetics, safety, tolerability, and immunogenicity between SB8, a bevacizumab biosimilar, and the European Union (EU) and United States (US) reference products (bevacizumab-EU, bevacizumab-US). METHODS: In this randomized, double-blind, parallel-group, and single-dose study, healthy volunteers were randomized to receive a 3 mg/kg dose of SB8, bevacizumab-EU, or bevacizumab-US via intravenous infusion. Primary endpoints were area under the concentration–time curve from time zero to infinity (AUC(inf)) and to the last quantifiable concentration (AUC(last)), and maximum observed serum concentration (C(max)). Bioequivalence was achieved if 90% confidence intervals (CIs) for the ratios of the geometric least squares means (LSMeans) of primary endpoints were within the predefined bioequivalence margins of 80.00–125.00%. Safety and immunogenicity were also investigated. RESULTS: The 90% CIs for the geometric LSMean ratios of AUC(inf), AUC(last) and C(max) were all within the prespecified bioequivalence margins. Geometric LSMean ratios for SB8/bevacizumab-EU, SB8/bevacizumab-US and bevacizumab-EU/bevacizumab-US were 88.01%, 88.48% and 100.54% for AUC(inf), 88.65%, 89.08% and 100.49% for AUC(last) and 99.59%, 101.15% and 101.56% for C(max), respectively. Incidence of treatment-emergent adverse events (TEAEs) across treatment groups was comparable (SB8: 50.0%, bevacizumab-EU: 37.5%, bevacizumab-US: 53.8%). Most TEAEs were mild and considered as not related to the study drug. No deaths or treatment discontinuations due to adverse events occurred. Incidence of anti-drug antibodies was also comparable between all groups and no neutralizing antibodies were detected. CONCLUSION: This study demonstrated pharmacokinetic bioequivalence and similar safety and immunogenicity profiles of SB8 to both reference products, bevacizumab-EU and bevacizumab-US, and of bevacizumab-EU to bevacizumab-US. CLINICALTRIALS.GOV IDENTIFIER: NCT02453672 (submitted date); EudraCT number: 2015-001,026-41.